“Community traditions, community kinship, language, and land bring me a lot of joy”: the importance of culture and social support in the health and wellbeing of Métis people - Heather J. A. Foulds; Jamie LaFleur; Shara R. Johnson; Samantha Moore; Adam McInnes; Leah J. Ferguson (International Journal of Qualitative Studies on Health & Well-Being)
Canada legally recognizes three Indigenous identities: First Nations, Inuit, and Métis. Métis People are a distinct Indigenous nation with unique history, culture, and traditions. Historic and ongoing colonization and assimilation policies negatively affect Indigenous Peoples’ mental, physical, emotional, cultural, and social health. Colonization and assimilation impacts on Métis People specifically are unclear, but health impacts and experiences differ from First Nations’. Objective The purpose of this narrative study was to understand Métis adults’ stories of culture and social support in relation to their health and wellbeing. Methods In partnership with Saskatoon Métis Local 126, 19 adults (9 females, 30 ± 11 years) participated in conversational interviews and photovoice reflections. Results Four themes represent the importance of culture and social support to Métis People’s health: 1) Métis Identity: “It was really empowering to learn about where I come from”; 2) Kinship, Community, and Culture: “Métis are people who gather”; 3) The Métis Environment and Land Connection: “Where I go to recharge”; 4) Knowledge, Impacts, and Intentional Steps for the Future: “Taking what’s good and making that in a way forward”. Conclusions Culture and social support are important protective factors in facilitating positive health outcomes for Métis People.